Profitability In Fish Breeding Business: A Case Study Of As-Syifa Pond Fisheries Business - Rina Mustika (Enrichment : Journal of Management, 2022)
As-Syifa Pond Fishery Business is located in Banjar Regency. It is engaged in a fish hatchery to help meet the needs of fish seed in South Kalimantan, which so far relies mainly on fish seed from the island of Java. This study aims to examine the profitability of a fish hatchery business in more depth. The research method used is a case study on the As-Syifa Pond fishery business. The data collected includes primary data and secondary data. The data obtained were then processed and analyzed descriptively, qualitatively, and descriptively quantitatively. The analysis used to answer the profitability of the fish hatchery business is Profit analysis, Revenue Cost Ratio (R/C) analysis, Break-Even Point (BEP) analysis, and Payback Period (PP) analysis. The results showed that the fish hatchery business in the As-Syifa Pond Fisheries Business was profitable and feasible to develop, so this business could be a model for other fish farmers to do fish hatchery business can also increase income and welfare for the community.